PTU-160 So You Requested Coeliac Serology; What Next?: A Seven Year Review Of Outcome After Requesting Anti-tissue Transglutaminase. (9th June 2014) - Johnson, MW; Housley, D; Gordon, D; Rostami, K
Abstract : Introduction: Coeliac disease is common in the UK with a prevalence of 1 in every 100–200 of the population. Individuals may go undetected for many years, despite presenting numerous times to both primary and secondary care. Some of the delay in diagnosis and missed diagnoses, may reflect that fact that coeliac disease can be asymptomatic or present with very subtle gastrointestinal symptoms. Serological testing is simple and accurate with studies suggesting sensitivity and specificity to be in the order of 95–98% and 95–97%, respectively. Not surprisingly therefore biochemistry laboratories throughout UK receive a substantial number of requests for coeliac serological assessments every year. Objective: We set out to review the total number of requested anti-endomysial antibody (AEAs) and anti-tissue transglutaminase (ATTG) tests between 2007 and 2013 at a busy district general hospital, and reviewed the outcome of having made that request. Methods: The results of all the coeliac serology requests made during the study period were reviewed and a retrospective analysis was made of the hospital records to find out the outcome in all those patients with positive results. The laboratory issued a positive result if the ATTG was greater or equal to 4. Results: During 2007, 810 AEAs were requested, of which 30 (3.7%) were positive (10 were weak positive), 736 were negative, 44 were not done. In 2008 ATTG became the primary coeliac serology test and AEAs were only used to review gluten free dietary (GFD) compliance. Between Jan 2008 and Dec 2013 a total of 20, 677 ATTGs were requested. This has steadily increase year on year. In 2008 there were 913 requests, 1, 389 in 2009, 3, 060 in 2010, 4, 238 in 2011, 5, 584 in 2012 and 6, 483 in 2013. Of these 785 (3.6%) proved positive, 19891 were negative, 372 samples were deemed insufficient and 605 were rejected by the laboratory as not indicated. Histological confirmation of coeliac disease was made in 222 patients, however a large proportion of positive serology received no further assessment. Conclusion: There is an ever increasing number of requests for coeliac serology, costing our local CCG £21, 070 in 2013. Despite the positive pick up rate being high at 3.6%, a large number of positive results were not pursued any further, with patients failing to have a definitive diagnosis made. It is important to ensure that there are robust mechanisms of chasing up on hospital results, and acting on them appropriately to prevent delayed or missed diagnoses. Disclosure of Interest: None Declared.